2012
DOI: 10.1097/meg.0b013e3283543f01
|View full text |Cite
|
Sign up to set email alerts
|

Regular statin and aspirin use in patients with Barrett’s oesophagus is associated with a reduced incidence of oesophageal adenocarcinoma

Abstract: In this observational case-control study, the regular use of statins was associated with a reduced incidence of OAC. The chemopreventative actions of statins, especially in conjunction with aspirin, deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 46 publications
0
63
0
Order By: Relevance
“…The differences between the groups were quantified using the calculated odds ratios and 95% confidence intervals, with the significance level set at P < 0.05. Unconditional logistic regression was used to correct for potentially confounding 8 factors: age, smoking, alcohol use, body mass index, waist circumference and all prescribed and over the counter mediations recorded (14,15,19).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The differences between the groups were quantified using the calculated odds ratios and 95% confidence intervals, with the significance level set at P < 0.05. Unconditional logistic regression was used to correct for potentially confounding 8 factors: age, smoking, alcohol use, body mass index, waist circumference and all prescribed and over the counter mediations recorded (14,15,19).…”
Section: Discussionmentioning
confidence: 99%
“…The main strengths of our study are the accurate and full records of medication exposure as reported previously (14,15,23) and the ability to correlate this with clearly defined endoscopic findings within the context of an adequately powered study. The main weakness, inherent in any observational study, is that of uncorrected bias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations